FORMAT PRODUKSI DESAIN BAJU KAOS ACO DI MAKASSAR - Absri, Absri; Anwar, Gusnawaty (JURNAL ILMU BUDAYA, 2015)
The proliferation of creative industries in the field of shirt is a container aspiration of the people in expressing social symbols. This study aims to determine the shape and design of the message and formatof production in the manufacture of shirts Aco Makassar. This research is conducted in Makassar precisely in store of Aco as a manufacturer shirt. The population of the study is all Aco T-shirt designsthat have been produced. Purposively selected sample are 25 T-shirt designs. The data are collected by using the techniques of observation, interviews and documentation. Data are analyzed descriptively usingPierce semiotic approach and the theory of Goffman footing.Results of this study found that the shape of a T-shirt design in Makassar Aco visually and verbally consists of icons, indexes and symbols. Another finding in this study is that there are five meaning of themessages to be conveyed in the design of a T-shirt Aco Makassar, namely (1) socialization of Makassar to the world, (2) introduced Bugis-Makassar, (3) introduced the culture of Bugis-Makassar, (4) introducedtypical culinary of Makassar, and (5) introduced attractions in Makassar. In general the design is in Makassar Aco shirt intends to raise and introduce the culture in South Sulawesi, especially culture Bugis-Makassar.Keywords: Semiotic, T-shirt, Makassar.